تحليل أهمية الموازنة العامة في الاقتصاد العراقي للمدة 2004-2020: تحليل أهمية الموازنة العامة في الاقتصاد العراقي للمدة 2004-2020 - Arbat, Ali (The Gulf Economist, 2023)
The research aims to present and analyze the structure of the public budget in the Iraqi economy for the period 2004-2020, through revenues and expenditures, since the budget reflects the total economic activity of the state, although it did not reflect the real goals of the state, but there was an absence of general goals such as working on diversifying revenues the public sector, which is a tool for translating economic and political goals, as well as limiting expenditures, eliminating unemployment and reducing the rate of inflation, just as the Iraqi economy is still dependent on its oil revenues to finance public spending, and this is what makes the economy vulnerable to shocks and external changes affecting oil prices. Accordingly, a development policy must be adopted for the purpose of achieving its basic objectives, such as economic diversification, reducing unemployment, and others.